Nudity, Sexuality, Photography. Visual Redefinition of the Body - Ferenc, Tomasz (Qualitative Sociology Review, 2018)
The article examines the relations between photography, body, nudity, and sexuality. It presents changing relations of photography with a naked or semi-naked body and different forms and recording conventions. From the mid-19th century the naked body became the subject of scientifically grounded photographic explorations, an allegorical motif referring to painting traditions, an object of interest and excitement for the newly-developed “touristic” perspective. These three main ways in which photographs depicting nudity were being taken at that time shaped three visual modes: artistic-documentary, ethnographic-travelling, and scientific-medical. It has deep cultural consequences, including those in the ways of shaping the notions of the corporeal and the sexual. Collaterally, one more, probably prevalent in numbers, kind of photographical images arose: pornographic. In the middle of the 19th century, the repertoire of pornographic pictures was already very wide, and soon it become one of the photographic pillars of visual imagination of the modern society, appealing to private and professional use of photography, popular culture, advertisement, art. The number of erotic and pornographic pictures rose hand over fist with the development of digital photography. Access to pornographic data is easy, fast, and cheap, thanks to the Internet, as it never was before. Photography has fuelled pornography, laying foundations for a massive and lucrative business, employing a huge group of professional sex workers. How all those processes affected our imagination and real practices, what does the staggering number of erotic photography denote? One possible answer comes from Michel Foucault who suggests that our civilization does not have any ars erotica, but only scientia sexualis. Creating sexual discourse became an obsession of our civilization, and its main pleasure is the pleasure of analysis and a constant production of truth about sex. Maybe today the main pleasure is about watching technically registered images, and perhaps that is why we may consider visual redefinition of the body as the main social effect of the invention of the photography.